Cardiac Structural and Functional Changes Evaluated by Transthoracic and Tissue Doppler Echocardiography in Adult Patients with Sickle Cell Disease - Dabirian, Mojdeh; Janbabaei, Ghasem; Karami, Hossein; Nabati, Maryam; Aarabi, Mohsen; Namazi, Morteza; DarvishiKhezri, Hadi (Acta informatica medica, 2017)
One of the most common genetic blood disorders, resulting from inherited red blood cell disorders, is sickle cell disease (SCD) which is responsible for high death in adult patients with left ventricular diastolic dysfunction and pulmonary hypertension. Tissue Doppler Echocardiography (TDE) and transthoracic echocardiography (TTE) are two useful tools to assess the risk of SCD. The present study was conducted to evaluate the cardiac functions and structure using TDE and TTE among adult patients suffering from sickle cell anemia compare to normal samples. The current study was performed on 30 SCD patients with a mean age 18-40 years and healthy cases at Mazandaran Heart Center, Iran. The left and right ventricular functions were assessed using M-mode, two-dimensional (2D), and tricuspid regurgitation jet velocity (TRJV) data and TDE derived myocardial velocity measurements in: SCD patients compared to control. According to the findings, SCD group showed significantly higher E and E' waves of left ventricle inflow compare to the control group (p<0.03 and p<0.01, respectively). No significant difference was observed for E/E' ratio between two groups: case and control, but there was significant differences between the groups in E and E' waves respectively equal to 8.55 and 8.14 cm/s. We obtained significant differences for peak early and late LV diastolic velocity between two groups and other indicators showed no significant differences. The evaluation of LV systolic and diastolic function via TDE did not indicate significant differences between SCD patients compared to healthy subjects. High E and E' waves in these patients, could indicate progression towards cardiac disorders and pulmonary hypertension in future.